Prioritizing barriers to be solved to the implementation of reverse logistics of e-waste in Brazil under a multicriteria decision aid approach - Vieira, Bárbara de Oliveira (2020)
This study aims to identify the main barriers to fully implement the reverse logistics of e-waste in Brazil and prioritize them under a Multicriteria Decision Aid approach (MCDA) according to the perceptions of small and medium-sized companies, consumers, and the Brazilian government. Hence, the study was conducted in two steps: (i) Systematic literature review to identify the main barriers, with data collection carried out through a documental analysis, and (ii) MCDA application, through self-administered questionnaires. In order to deal with the uncertainty in subjective measures, the method of Composition of Probabilistic Preferences (CPP) was applied to analyze the results of each group of decision maker, opting for the progressive-pessimistic scenario to prioritize the barriers to be solved. As main results, a priority classification of the internal and external barriers considering each category of decision maker was obtained. Moreover, it was verified that the government and micro and small companies agreed that internal barriers with an organizational nature or related to infrastructure management are the main obstacles to the implementation of reverse logistics. On the other hand, consumers consider the managerial or organizational barriers as a priority.